Obtaining carvacrol from Origanum onites L. essential oil and developing carvacrol-loaded nanoformulation for use in cosmetics - Aydin, Tugba; Gok, Bahar; Budama-Kilinc, Yasemin; Kartal, Murat (ELSEVIER, 2025)
Carvacrol (Car) is a major component of Origanum species with many biological activities. This study aims to obtain the Car extract from Origanum onites L. essential oil and its formulation into polycaprolactone (PCL) nanoparticles (NPs) for potential use as an anti-aging formulation in the cosmetic industry. Car extract was obtained from essential oil and its purity was determined by GC-MS. Car-PCL-NPs were produced using the single emulsion method, and characterized by Dynamic Light Scattering (DLS), UV-Vis spectroscopy and Scanning Electron Microscopy (SEM). The anti-collagenase activity of the formulation, its toxicity in cell culture, and its safe dose were determined. According to the results, the Car was identified at a rate of 85.021 %. The average particle size (APS) of Car-PCL-NPs was 199.5 f 0.91 nm, the polydispersity index (PdI) was 0.070 f 0.015, and the zeta potential (ZP) was -8.51 f 0.76 mV. The encapsulation efficiency and loading capacity of Car-PCL-NPs were 98.55 % and 20 %, respectively. In vitro controlled release study was carried out, and it was determined that 95.55 % of Car was released from Car-PCL-NPs in 48 h. Moreover, it was found that Car-PCL NPs exhibited almost twice as much anti-collagenase activity compared to free Car. In addition, as a result of the in vitro cytotoxicity study conducted on the HaCaT cell line, it was determined that free Car showed toxic effects even at the lowest concentration of 0.125 mg/mL. However, encapsulation with PCL markedly enhanced the biocompatibility of Car, resulting in Car-PCL-NPs demonstrating 81.45 f 1.84 % cell viability at a concentration of 1 mg/mL. In conclusion, the successfully synthesized Car-PCL-NPs, exhibiting anti-collagenase activity and biocompatibility, may be regarded as potential anti-aging product candidates in the cosmetic industry.
Keywords: Origanum onites L.; Carvacrol; Polycaprolactone; Nanoparticle; Anti-collagenase activity; In vitro cell culture; ANTIMICROBIAL ACTIVITY; NANOPARTICLES; ENCAPSULATION; OREGANO; SKIN; Agriculture